PENERAPAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING (PBL) DALAM MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS IV SEKOLAH DASAR - Julhidayat Muhsam; Abdul Syahril Muh (Program Studi Teknologi Informasi, Universitas Muhammadiyah Muara Bungo, 2022)
The purpose of this study is to improve the learning outcomes of fourth grade students of SDI Siumolo, Kupang Regency by applying the PBL learning model. The type of research used in this research is Classroom Action Research (CAR). The subjects of this study were fourth grade students, with a total of 20 students consisting of 13 male students and 7 female students. The research was carried out in a cycle starting from cycle one to completion with the planning stage, implementation stage, observation stage, and reflection stage. Data collection techniques used in this study were observation and learning outcomes tests. From the results of the first cycle the average score was 67.75, with a completeness percentage of 55%, the results of observing student activities were 73.33 (enough) and the results of observing teacher activities were 76.78 (enough). After the second cycle obtained an average value of 81.75 with a percentage of completeness that is 90%, the results of observing student activities are 85.10 (Good) and the results of observing teacher activities are 96.42 (Good). Thus, student learning outcomes and the results of the analysis of observational observation sheets increase towards a better direction with the application of PBL learning models compared to using the lecture method.